2022
DOI: 10.3390/ijerph191811461
|View full text |Cite
|
Sign up to set email alerts
|

Competencies of Nurse Managers as Predictors of Staff Nurses’ Job Satisfaction and Turnover Intention

Abstract: Nurse managers have played an integral role in stabilizing the nursing work environment and workforce in the face of the COVID-19 pandemic, yet the competencies required for such a feat are largely unknown. This study was conducted during the pandemic to identify the specific domains of nurse manager competencies that associate with nurse outcomes. A cross-sectional survey was conducted on a convenience sample of 698 staff nurses to measure the perceived competence of their nurse managers and their job satisfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…The authors have not found any research results depicting the job satisfaction of nurses in early 2023. However, job satisfaction among nurses during the first and second years of the pandemic was found to have decreased (Choi et al, 2022 ; Piotrowski et al, 2022 ; Ribeiro et al, 2022 ). This decline in satisfaction is attributed to the conditions of the COVID-19 pandemic, as evidenced by the study of Labrague and de Los Santos ( 2021 ) in the Philippines, which found a significant correlation between nurses’ fear of COVID-19 and decreased job satisfaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors have not found any research results depicting the job satisfaction of nurses in early 2023. However, job satisfaction among nurses during the first and second years of the pandemic was found to have decreased (Choi et al, 2022 ; Piotrowski et al, 2022 ; Ribeiro et al, 2022 ). This decline in satisfaction is attributed to the conditions of the COVID-19 pandemic, as evidenced by the study of Labrague and de Los Santos ( 2021 ) in the Philippines, which found a significant correlation between nurses’ fear of COVID-19 and decreased job satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has consistently demonstrated that the pandemic has led to unsatisfactory levels of job satisfaction among nurses. For instance, findings from Hong Kong indicated that approximately 35% of nurses expressed dissatisfaction with their jobs during the pandemic (Choi et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Determining the professional competence level can assist clinical nurses and stakeholders in identifying areas that require additional development to improve their competence. This, in turn, can improve patient care, raise patient satisfaction, and lower morbidities (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Such roles are associated with strong academic qualifications and/or years of experience that translates to provision of patient safe care. As nurse leaders, nurse manager competencies were, in a study by Choi et al (2022) [2] found to be directly related to the nurse outcomes, whereby five key domains of nurse manager competences (staff advocacy and development, team communication and collaboration, change and resource management, quality monitoring and pursuance, and personal mastery) directly affected job satisfaction.…”
Section: Introductionmentioning
confidence: 99%